Analysis Of Protection Relay Setting Coordination On Excitation Transformer At Gresik PLTGU - Muhamad Ainul Yaqin; Royb Fatkhur Rizal (International Journal of Health Engineering and Technology, 2026)
Excitation transformer is one of the important equipment in the generation system that functions to supply generator excitation power so that the reliability of the transformer protection system needs to be maintained so that the generator operation remains safe and stable. This study aims to analyze the coordination of protection relay settings on the excitation transformer at the Gresik PLTGU using the GE Multilin T60/G60 relay. The analysis was carried out based on the existing relay settings without using a full system simulation, with a focus on the evaluation of differential protection (ANSI 87T), overcurrent relay (ANSI 51), overexcitation protection (ANSI 24), and the inrush inhibit feature. The research method used is descriptive-analytical through data collection in the form of single line diagrams, current transformer (CT) data, and existing relay settings which are then compared with the IEEE C37.91, IEC 60255 standards, and the GE Multilin T60 relay manual. The results of the study indicate that the differential relay settings with a pickup of 0.3 pu, slope 1 of 30%, slope 2 of 80%, and inrush inhibit of 20% are still within the recommended range of transformer protection and are able to maintain the sensitivity and stability of the relay against internal disturbances and transient conditions. The overcurrent relay setting of 2 pu with a delay of 3 seconds and instantaneous overcurrent of 4 pu with a delay of 0.15 seconds shows a fairly selective backup protection coordination against overcurrent and short circuit disturbances. In addition, the overexcitation setting of 1.19 pu with a delay of 10 seconds is considered still appropriate to protect the transformer from overfluxing conditions. Based on the evaluation results, the transformer excitation protection system at the Gresik PLTGU has had quite good protection coordination according to the principles of sensitivity, selectivity, stability, and reliability of the transformer protection system.